2018
DOI: 10.1051/limn/2018024
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal dynamics of Zooplankton functional groups in relation to environmental variables in Xiquanyan Reservoir, Northeast China

Abstract: In this study, the concept of functional feeding groups was used to classify and model the seasonal variation of zooplankton functional groups in relation to environmental variables. A total of 48 zooplankton species were observed in the reservoir and grouped into 8 functional groups. Both environmental variable and the biomass of zooplankton functional groups vary spatially and seasonally. Water temperature, water transparency, total nitrogen and nitrates were significantly higher in summer, while chlorophyll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 55 publications
3
10
2
Order By: Relevance
“…Metabarcoding technology can also detect distinct seasonal patterns of taxa that are generally not detectable using traditional methods (Banerji et al, 2018).The analysis shows that the zooplankton community has obvious seasonal changes in Sanmenxia Reservoir. This finding is consistent with previous studies of significant seasonal changes in the zooplankton community based on traditional morphological monitoring and metabarcoding techniques in other freshwater reservoirs (Mwagona, Chengxue & Hongxian, 2018;Nandini, Merino-Ibarra & Sarma, 2008;Tan et al, 2004;Vanderploeg et al, 2012) However, the relative abundance identified for Cladocera did not differ significantly between seasons despite its relative abundance in COI being significantly higher than that in 18S. According to reports, the seasonal changes in Cladocera were controlled by the seasonal changes in nutrients (Xiao-Jun et al, 2014).…”
Section: Seasonal Changes In the Zooplankton Communitysupporting
confidence: 91%
See 1 more Smart Citation
“…Metabarcoding technology can also detect distinct seasonal patterns of taxa that are generally not detectable using traditional methods (Banerji et al, 2018).The analysis shows that the zooplankton community has obvious seasonal changes in Sanmenxia Reservoir. This finding is consistent with previous studies of significant seasonal changes in the zooplankton community based on traditional morphological monitoring and metabarcoding techniques in other freshwater reservoirs (Mwagona, Chengxue & Hongxian, 2018;Nandini, Merino-Ibarra & Sarma, 2008;Tan et al, 2004;Vanderploeg et al, 2012) However, the relative abundance identified for Cladocera did not differ significantly between seasons despite its relative abundance in COI being significantly higher than that in 18S. According to reports, the seasonal changes in Cladocera were controlled by the seasonal changes in nutrients (Xiao-Jun et al, 2014).…”
Section: Seasonal Changes In the Zooplankton Communitysupporting
confidence: 91%
“…DNA metabarcoding technology provides detailed information about zooplankton biodiversity and can support biodiversity conservation (Xiong et al, 2020). In addition, it has been successfully used to track seasonal changes in the zooplankton community (Berry et al, 2019;Mwagona, Chengxue & Hongxian, 2018;Nandini, Merino-Ibarra & Sarma, 2008;Tan et al, 2004;Vanderploeg et al, 2012). Metabarcoding technology sensitively reflects the relationship between the abundance of the zooplankton community and environmental factors and provides methodological support for exploring the water environmental factors that drive seasonal changes in zooplankton (Yang et al, 2017a).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the biomass of zooplankton functional groups varied significantly differences among seasons and sites. The mean values of biomass reported in spring (0.91 mg/L), summer (1.70 mg/L) and autumn (0.79 mg/L) were higher than those recorded by Mwagona et al (2018) in the oligotrophic Xiquanyan Reservoir during spring (54.25 µg/L), summer (245.81 µg/L) and autumn (196.54 µg/L) and also higher than those found by Ma et al (2019) in Small Xingkai Lake during spring (0.28 mg/L) and autumn (0.72 mg/L) in the same province. Mwagona et al (2018) found that low nutrients level, which unable to meet the demand of the growth of zooplankton.…”
Section: Composition and Variations Of Zooplankton Functional Groups In Tuanjie Reservoircontrasting
confidence: 60%
“…In Western English channel, the researchers analyzed the food web using three zooplankton functional groups (Araújo et al, 2006). On the other hand, in freshwater ecosystems, six and eight zooplankton functional groups have been confirmed in Small Xingkai Wetland Lake and Xiquanyan Reservoir in Heilongjiang Province, Northeast of China, respectively (Ma et al, 2019;Mwagona et al, 2018). In our study, we identified 30 species belonging to seven zooplankton functional groups in Tuanjie Reservoir, including group PF, RF, SCF, MCC, MCF, LCC and LCF.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation